DETERMINANTS OF INFLATION: Monetary and Macroeconomic Perspectives - Ridwan, Muhammad (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2022)
Inflation comes at any time, from anywhere, and cannot be controlled. However, we can make an effort to minimize it, through controlling a number of economic instruments, such as the monetary sector. We need to manage how the financial aspects can be controlled, both money circulating in the community, money in transactions (exports and imports), and money in savings. On this basis, this study is interested in disclosing several monetary factors that affect inflation. The method used in this research is quantitative, with regression analysis. Secondary data is used as a way of analyzing phenomena. The sampling technique uses a purposive type, namely the use of data based on predetermined criteria. The results of the study explain that inflation occurs over a long period of time, slowly. Financial and economic factors become one of the instruments that have an impact on inflation. So do not be surprised, if in every change, both economic and financial aspects, always correlated with inflation.